Effects of allyl isothiocyanate on insulin resistance, oxidative stress status, and transcription factors in high-fat diet/streptozotocin-induced type 2 diabetes mellitus in rats - Sahin, Nurhan; Orhan, Cemal; Erten, Fusun; Tuzcu, Mehmet; Deeh, Patrick B. Defo; Ozercan, Ibrahim H.; Kazim, Sahin (Wiley, 2019)
Allyl isothiocyanate (AITC), a dietary phytochemical found in some cruciferous vegetables, is commonly used as an antimicrobial, anticancer, and antioxidant agent. In the present study, we investigated the effects of AITC on insulin resistance and transcription factors in a diabetic rat model. A total of 42 Wistar rats were divided into six groups and orally treated for 12 weeks as follows: (i) control; (ii) AITC (100 mg/kg body weight [BW]); (iii) high fat diet (HFD); (iv) HFD + AITC (100 mg/kg BW); (v) HFD + streptozotocin (STZ, 40 mg/kg BW); and (vi) HFD + STZ + AITC. Administration of AITC reduced blood glucose, total cholesterol, triglycerides, and creatinine levels, but increased (P < 0.001) total antioxidant capacity. In AITC-treated rats, the glucose transporter-2, peroxisome proliferator-activated receptor gamma, p-insulin receptor substrate-1, and nuclear factor erythroid-derived 2 in the liver and kidney were increased while nuclear factor-kappa B was downregulated (P < 0.05). In conclusion, AITC possesses antidiabetic, antioxidant, and anti-inflammatory activities in HFD/STZ-induced T2DM in rats. These findings may further justify the importance of AITC in phytomedicine.
Keywords: allyl isothiocyanate; diabetes; insulin resistance; oxidative stress; streptozotocin